In Search of the Missing Links Between Economic Insecurity and Political Protest: Why Does Neoliberalism Evoke Identity Politics Instead of Class Interests? - Siltala, Juha (Frontiers in Sociology, 2020)
The prospect of the social backsliding of middle-class groups in western countries has not benefited the left but fueled right-wing populism. This article examines mediating and moderating factors between economic threat and political choices. The shift of liberals towards conservatism and the activation of passive authoritarians explain sudden changes more than dispositional factors. Attachment to groups under stress activates coalitional mindsets, and coalitional competition for scarce resources matches the conservative propensity to detect threats from outgroups. Risk-averse right-wing authoritarians should recoil from social-dominance oriented risk-takers but they follow winners despite their mutual differences concerning family values. Successful businessmen and Mafiosi are selected as leaders, since they promise booty for their followers, too: evolutionary adaptation may explain their appeal. Moreover, they offer identification with the aggressor and thus overcoming victimization. This transforms individual anxieties into fight and flight activity. Authoritarian aggression unites the right-wing authoritarians and the social-dominance oriented, but politically passive right-wing authoritarians can also follow their economic interests, when these are not entangled with cultural values. Right-wing populists have been able to compensate economic insecurity with epistemic security. Identity politics supports the coherence of right-wing populist parties but divides leftist/liberal groups due to intersectional tensions.